A randomized head-to-head study of small-bowel imaging comparing MiroCam and EndoCapsule - Dolak, W.; Kulnigg-Dabsch, S.; Evstatiev, R.; Gasche, C.; Trauner, M.; Püspök, A. (Endoscopy, 2012)
Background and study aims: The MiroCam is a new video capsule device offering a higher frame rate and a longer battery life-expectancy. We aimed to quantify its clinical impact and performed a randomized head-to-head comparison with the EndoCapsule device with respect to the rate of complete small-bowel examinations, diagnostic yield in the small bowel, and capsule transit time.Patients and methods: Patients referred for video capsule endoscopy because of obscure gastrointestinal bleeding, chronic diarrhea, and anemia of unknown origin were randomly assigned to swallow either the MiroCam first, followed by the EndoCapsule 2 hours later, or vice versa. All videos were analyzed by two independent investigators. Results: A total of 50 patients (median age 61, range 21 – 84) were included. Complete small-bowel examination was achieved in 48 /50 patients using the MiroCam and 45 /50 using the EndoCapsule (96 % vs. 90 %, odds ratio [OR] 2.67, 95 % confidence interval [CI] 0.49 – 14.45; P = 0.38). There was diagnostic yield in the small bowel for 25 /50 patients using the MiroCam and 24 /50 using the EndoCapsule (50 % vs. 48 %, OR 1.08, 95 %CI 0.49 – 2.37; P > 0.99). However, the findings were concordant in 68 % only (kappa = 0.50). The combined diagnostic yield was 58 %. Even solitary findings had a relevant clinical impact during a 6-month follow-up.Conclusion: In this direct comparison the MiroCam and EndoCapsule devices were not statistically different with regard to their rates of complete small-bowel examinations or diagnostic yield. Their moderate concordance, mainly caused by missed pathological findings, which affected both devices, needs consideration in clinical practice.